Factors Affecting Inpatient Mortality in Elderly People with Acute Kidney Injury - Muhammad Abdul Mabood Khalil; Safia Awan; Rabeea Azmat; Muhammad Ashhad Ullah Khalil; Nazish Naseer; Jackson Tan (The Scientific World Journal)
Background. Acute Kidney Injury (AKI) is common in elderly people (EP). There is paucity of data on predictor of mortality in EP with AKI. Objective. This study was done to know more about factors associated with inpatient mortality in EP with AKI. Methods. We retrospectively reviewed medical records of patients aged 65 years or above hospitalized with a diagnosis of AKI at Aga Khan University Hospital, Karachi, between January 2005 and December 2010. Binary logistic regression models were constructed to identify factors associated with mortality in EP with AKI. Results. 431 patients had AKI, with 341 (79.1%) having stage I AKI, 56 (13%) having stage II AKI, and 34 (7.9%) having stage III AKI. Out of 431 patients, 142 (32.9%) died. Mortality increased with increasing severity of AKI. Mortality was 50% (17/34) in AKI stage III, 44.6% (25/56) in AKI stage II, and 29.3% (100/341) in AKI stage I. Factors associated with increased inpatients mortality were presence of stage III AKI (OR: 3.20, P=0.04, 95% CI: 1.05–9.72), presence of oliguria (OR: 3.42, P=0.006, 95% CI: 1.42–8.22), and need for vasopressors (OR: 6.90, P<0.001, 95% CI: 2.42–19.65). Median bicarbonate 18 versus 17 between those who survived and those who died was associated with less mortality (OR: 0.94, P=0.02, 95% CI: 0.89–0.99). History of hypertension (OR: 0.49, P=0.03, 95% CI: 0.25–0.95) and high admission creatinine (OR: 0.68, P=0.01, 95% CI: 0.50–0.91) were also associated with less mortality. Conclusion. Mortality in EP increases with increasing severity of AKI. Presence of stage III AKI, oliguria, and hemodynamic instability needing vasopressor are associated with increased mortality. Increased median bicarbonate, presence of hypertension, and high admission creatinine were various factors associated with decreased inpatient mortality. Increasing age and need for dialysis did not increase mortality in elderly population.